PENGARUH FREKUENSI PEMBERIAN TES TERHADAP MEMORI JANGKA PANJANG BACAAN PADA SISWA SMA - Santi Jayani; Thomas Dicky Hastjarjo (University of Merdeka Malang, 2011)
ABSTRACT This Experimental Research was aimed to examine the effect of giving frequent test (three times test, once test, and without test) to long term memory of reading text to Senior High School student. Experiment design was Mixed Factorial Designs with three groups that got different treatment condition. The first group got once time to study and three times test (STTT), the second group got three times to study and once time test (SSST), and the third group got four times to study without test (SSSS). Long term memory of reading text was measured by reading text recall test. Subjects of this research were ninety student of LTI IGM Senior High School Palembang (consist of eleventh grade students of natural science and social science class). Subjects were randomized by SPSS random assignment. Data were analyzed by using Anova Mixed Design.The result of Anova Mixed Design showed that the hypothesis is proven by F = 5,636 and p = 0,005 (p0,05) which means there was effect of test to reading text. Further analysis by using LSD showed (MD) = 1,12, p=0,031 (p0,05) which means three times test produce better long term memory than without test. Once time test that analyzed using LSD showed (MD)= 1,68, p=0,01 (p0,05) which means once time test produce better long term memory than without test. Long term memory produced by three times test was equal to once time test, showed by (MD)= -0,57, p=0,270 (p0,05). Keyword : Long term memory, reading text.